The Mediating Role of Attitude: Internships and Learning Achievement on Work Readiness - Rosalina Rahmawati; Brillian Rosy (Journal of Office Administration : Education and Practice, 2025)
Internships, learning achievement, and attitude are essential for every vocational high school student to enter the workforce in fields aligned by their competencies and areas of specialization. This study investigates the influence of internships and learning achievement on the work readiness of 12th-grade students at VHS YPI Darussalam 2 Cerme, with attitude examined as a mediating variable by 79 students. This study employed data collection through the distribution of questionnaires. The data analysis technique used was Partial Least Squares (PLS) analysis by SmartPLS that includes measurement model testing (outer model), structural model testing (inner model), and hypothesis testing. The findings show that internships significantly enhance work readiness, particularly through the development of discipline, which emerged as the strongest indicator of internship quality. Learning achievement also demonstrates a strong direct effect on work readiness. This study underscore the need for vocational schools to integrate structured internship programs, strengthen academic learning practices, and promote systematic character development. Well-designed collaboration between schools and industry is essential to ensure that students acquire both technical competencies and essential soft skills. The study affirms that a combination of strong academic performance, meaningful internship experiences, and positive attitudes forms the foundation of students’ successful transition into the workforce.